Promoting Justice through Membership Rights: Insights from International and Municipal Law - Nnawulezi, Uche; Mugisha, Cedric; Hakuzimana, Jean Damascene; Yesashimwe, Amina (Susbtantive Justice International Journal of Law, 2024)
The paper aims to examine how international law can be advanced through membership rights, with a particular focus on international organizations and municipal laws. It explores how treaty-based frameworks in international law facilitate cooperation among states, while municipal law operates within the sovereign jurisdiction of individual states. The paper highlights key distinctions in the regulation and enforcement of membership rights within these two systems. It may be argued that while international organizations provide a platform for collective action on global issues, enforcement mechanisms remain limited due to the lack of centralized legislative or executive authorities. These structural limitations create disparities among states, where weaker states may face indirect subjugation in the face of international negotiations. The paper employs a doctrinal approach by identifying and analyzing relevant treaties, laws, case law, and scholarly works. It demonstrates how international and municipal legal systems intersect, especially through human rights treaties, which enable individuals to access global judicial mechanisms. The paper reveals that, despite the existence of global justice mechanisms, enforcement remains challenging due to power imbalances and concerns over state sovereignty. Reservations made by states to international treaties further undermine the effectiveness of these frameworks. The paper concludes with recommendations to strengthen the legal frameworks governing membership rights. These include eliminating state reservations to international treaties, enhancing enforcement mechanisms under international legal frameworks, and ensuring equitable participation by all member states. These measures are necessary to harmonize international and municipal legal systems for the better protection and promotion of human rights.